Pancreas transplantation - E. V. Usova; M. M. Kaabak; A. V. Chzhao (Трансплантология (Москва), 2016)
Literature data analysis in pancreas transplantation (Tx) is represented in the article. Its history is described. Advantages and disadvantages of different Tx types and long term results are represented in detail. The problem of pancreatic islets Tx is briefly delineated.